Ubuntu, Zimbabwe and the ethics of intervention - De Jager, Peta (My University, 2010)
ABSTRACT The profound and extensive nature of difficulties in Zimbabwean current affairs raises a moral dilemma for South Africa: should it intervene in some way, or respect Zimbabwean sovereignty? Is there a plausible ‘middle ground’ theory to resolves this dilemma? This paper argues that there may well be. It further argues that such a ‘middle ground’ account is consistent with at least one version of ubuntu, an indigenous sub-Saharan African philosophy. What does ubuntu have to say about the right (or perhaps even the obligation) of the South African government to have intervened in Zimbabwean affairs? Does it vindicate South Africa for its failure to intervene? This project, whilst not providing a decisive answer to the question of whether intervention in Zimbabwe by South Africa is legitimate on this African world-view, provides one possible approach to evaluating the dilemma from an ubuntu-informed perspective.
Keywords: Ubuntu; ethics; Zimbabwe; intervention; sovereignty; South Africa; philosophy; applied ethics; international relations